A dual mortar contact method for porous media and its application to clay‐core rockfill dams. (2nd April 2019) - Wang, Wei; Zhou, Mozhen; Zhang, Bingyin; Peng, Chong
Summary: The clay‐core rockfill dam is a multibody contact system in which the hydromechanical response of the clay core plays a crucial role. This complex problem is highly challenging to model numerically. We present a numerical approach that considers the multibody contact, consolidation, and strong geometric and material nonlinearities for the modeling of clay‐core rockfill dams. Within the framework of the dual mortar finite element method, the presented approach considers the contact bodies as independent porous media continuums. The nonlinear contact conditions are derived based on the effective contact traction on contact interfaces and pore pressure continuity. The weak forms are obtained by introducing Lagrange multipliers as additional unknowns, which are then condensed through an extended general transformation. The presented method is first validated with a patch test considering the contact between two porous media. Then, a three‐dimensional analysis of the Rumei clay‐core rockfill dam is performed. The main numerical analysis concerns are the two observation galleries planned for construction inside the clay core. The galleries consist of dozens of tunnel‐like concrete blocks, giving rise to complex concrete‐concrete and concrete‐clay contacts. The discontinuous separation and sliding between concrete blocks are investigated. For the concrete‐concrete contact, both hard and soft joint approaches are evaluated and compared. The pore pressure results of the concrete structures are also analyzed.